Consideraciones metodológicas para la síntesis automática de procesadores difusos en ANSI-C - Forero, Edgar; Garcia, Edgar; Melgarejo Rey, Miguel Alberto (Ingeniería, 2008)
This paper presents some methodological considerations for developing an automatic tool that generates specifications of fuzzy processors. Our considerations are presented generally so that they could guide the development of automatic tools for synthesizing fuzzy processors over different hardware technologies. Additionally, It is presented a particular case of an automatic tool that synthesizes fuzzy processors specified in a high-level description tool. Some practical results obtained by using this tool are presented and discussed.